FACIAL PROFILE ANALYSIS RESULTS ON PHOTOGRAPHY AND LATERAL CEPHALOGRAMS OF ORTHODONTIC PATIENTS IN FACULTY OF DENTISTRY UPDM - Aldila Rosanti; Pricillia Priska Sianita (Journal of Health and Dental Sciences, 2023)
The face and facial profile are the main parts of the body that can help a person form impressions and interact with other people in their environment. Both faces and facial profiles have some special characteristics that differentiate individuals. Analysis of a person's facial profile can be carried out by measuring the soft tissue profile at certain anatomical standard points as a reference and using photographic data (lateral facial photos of the patient) and radiographic (soft tissue profile in lateral cephalogram of the patient). This study was conducted to explain the differences in the facial profile analysis results performed on orthodontic patients' photographs and radiographs. A total of 44 orthodontic patients participated in this study, and by using the purposive sampling method, research materials were obtained in the form of photographs and lateral cephalograms of patients with skeletal class II malocclusion characteristics. The results of facial profile analysis on radiographs are smaller than those of facial profile analysis on photographs. In conclusion, it can be said that there is a statistically significant difference between the results of facial profile analysis on photographs and radiographs of orthodontic patients. DOI : 10.54052/jhds.v3n2.p197-206